IDENTIFIKASI MORFOLOGI FUNGI MIKORIZA ARBUSKULA (FMA) PADA BERBAGAI JENIS TANAMAN HORTIKULTURA DI LAHAN PERTANIAN DESA NUPABOMBA - Liana, Liana; Patadungan, Yosep Soge; Widjajanto, Danang (AGROTEKBIS, 2018)
The research aimed at identifying the morphology of mycorrhizal arbuscular fungi (MAF) on the root zones of different horticultural crops (peppers, potato, leek, cabbage, tomato and chicory) in Nupabomba village Tanatovea sub district of Donggala.  It was descriptive exploratory study and conducted from October to December 2015. Samples of soil were purposively taken around the root zone and analyzed for its chemical and physical characteristics as well as for mycorrhizae  spore isolation and its identification.  The research results showed that the highest spore number of 303 spores per 10 g was found in the leek plantation whereas the lowest number of 43 spores per 10 g in the potatoes plantation.  There are four types of spore genus i.e. Acaulaspora, Entrophospora, Glomus and Paraglomu.  The Glomus genus was the dominant spores found in all types of the horticultural plantations.